2012
DOI: 10.1136/heartjnl-2011-301399
|View full text |Cite
|
Sign up to set email alerts
|

Severe pulmonary regurgitation after tetralogy-of-Fallot repair: transcatheter treatment with the Edwards SAPIEN XT heart valve: Figure 1

Abstract: Chronic pulmonary regurgitation (PR) is a frequent condition after intracardiac repair of tetralogy-of-Fallot that affects up to 36% of long-term survivors. 1 2 Herein, we present the case of a 64-year-old female patient with severe symptomatic PR. She had undergone tetralogy-of-Fallot repair at the age of 17 including right ventricular (RV) outflow tract (RVOT) enlargement with a transannular patch. At the age of 59, the patient underwent tricuspid valve repair for severe tricuspid regurgitation.She now prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…37 Nedavna metaanaliza ishoda nakon zamjene pulmonalnog zaliska (PVR) koristi se podatcima o više od 3100 pacijenata te pokazuje da je ukupna 30-dnevna smrtnost iznosila 0,87%, a petogodišnja smrtnost 2,2%.…”
Section: -32unclassified
See 1 more Smart Citation
“…37 Nedavna metaanaliza ishoda nakon zamjene pulmonalnog zaliska (PVR) koristi se podatcima o više od 3100 pacijenata te pokazuje da je ukupna 30-dnevna smrtnost iznosila 0,87%, a petogodišnja smrtnost 2,2%.…”
Section: -32unclassified
“…Pulmonic valve regurgitation is one of the main causes of decreased RV function in patients with ToF, although it may be tolerated for decades in some individuals. 37 A recent meta-analysis of outcomes after pulmonary valve replacement (PVR) including the data from more than 3100 patients, demonstrated that pooled 30-day mortality was 0.87% and 5-year mortality was 2.2%. 38 The risk for re-PVR was estimated to be 4.9% after 5 years.…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%
“…Encouraging results were reported with the Edwards SAPIEN transcatheter valve for conduit failure in the pulmonary position in 36 patients from four centres 64. Helpful images of this device were published by Lauten et al 65. The outcomes of pre-stenting 1 year after using the Melody valve in the pulmonary position66 were reported in 65 patients.…”
Section: Catheter Interventionmentioning
confidence: 99%
“…Encouraging results were reported with the Edwards SAPIEN transcatheter valve for conduit failure in the pulmonary position in 36 patients from four centres. 64 Helpful images of this device were published by Lauten et al 65 The outcomes of pre-stenting 1 year after using the Melody valve in the pulmonary position were reported in 65 patients. The early haemodynamic results were sustained at 1 year, but there was no evidence of further positive functional remodelling after the immediate acute effects.…”
Section: Catheter Interventionmentioning
confidence: 99%